Unsteady phenomena in saturated flow boiling heat transfer – An experimental study on oscillating refrigerant mass flux - Wen-Ken Li (Elsevier, 2022)
The present work pertains to experimental studies on the unsteady phenomena in the saturated flow boiling of R407C stemming from the oscillatory refrigerant flow rate with the triangle shape in the horizontal slender annular channel. Attention is mainly paid to examine the effects of different parameters, including mean mass flux, amplitude and period of the oscillating mass flux, saturation temperature of R407C, input thermal flux, and gap size on the boiling diagrams and heat transfer coefficients. Firstly, the steady-state saturated flow boiling is studied as baseline cases. It was concluded that beyond the onset of nucleate boiling region, the mass flux of refrigerant has little influences on the boiling diagrams, which indicates that the fully developed nucleate boiling is the major mechanism. The saturated flow boiling heat transfer coefficient is enhanced as the gap size is reduced. Then, the experiment focuses on the temporal changes in the wall temperature Tw and the heat transfer coefficient hr stemming from oscillatory flow conditions. When the mass flux is oscillated periodically with the triangle shape, the Tw and hr are also oscillated temporally and enhanced with increasing in either the amplitude or frequency of oscillating mass flux. At higher input thermal flux, Tw decreases with the decreasing mass flux, which has opposite tendency compared to the single-phase convection with lower thermal flux. For intermediate exerted thermal flux, there is a negligible oscillation in the Tw and hr for most cases; the amplitudes of oscillations are lower than 0.2 °C. Besides, the significant oscillations in the wall temperature and heat transfer coefficient are noted the case with large period of the oscillating mass flux.